2009
DOI: 10.1007/s10021-009-9277-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Submerged Vegetation on Water Clarity Across Climates

Abstract: A positive feedback between submerged vegetation and water clarity forms the backbone of the alternative state theory in shallow lakes. The water clearing effect of aquatic vegetation may be caused by different physical, chemical, and biological mechanisms and has been studied mainly in temperate lakes. Recent work suggests differences in biotic interactions between (sub)tropical and cooler lakes might result in a less pronounced clearing effect in the (sub)tropics. To assess whether the effect of submerged ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 56 publications
(17 reference statements)
2
71
1
Order By: Relevance
“…Several studies have reported enhanced water clarity above charophyte vegetation (Scheffer et al, 1994;Hargeby et al, 2007), although this clearing effect is not limited to charophytes (Kosten et al, 2009b). Charophytes can attain high biomass and form dense stands (Blindow, 1992b;Van Nes et al, 2002;Bakker et al, 2010), which may improve the trapping of sediment.…”
Section: The Role Of Macrophyte Species In Ecosystem Stabilitymentioning
confidence: 99%
“…Several studies have reported enhanced water clarity above charophyte vegetation (Scheffer et al, 1994;Hargeby et al, 2007), although this clearing effect is not limited to charophytes (Kosten et al, 2009b). Charophytes can attain high biomass and form dense stands (Blindow, 1992b;Van Nes et al, 2002;Bakker et al, 2010), which may improve the trapping of sediment.…”
Section: The Role Of Macrophyte Species In Ecosystem Stabilitymentioning
confidence: 99%
“…Re-analysing the data from Canfield Jr et al (1984) cited by Dolman (2014) and suggesting a strong effect of macrophytes in subtropical lakes, we found no significant contribution of submersed macrophytes to increasing the coefficient of determination of Chl a -TP regression and the ratio differed slightly (P = 0.74) between vegetated and non-vegetated lakes with overlapping TP ranges. In conclusion, the only four relevant works on subtropical lakes we could find in literature (Bachmann et al, 2002 andKosten et al, 2009 being the other two) all suggest weaker effects of macrophytes on algal turbidity than in temperate lakes.…”
mentioning
confidence: 66%
“…Thus the influence of fish on nutrient cycles could be greater during warmer seasons and at warmer latitudes. However, biomanipulations may actually be less effective at warmer latitudes because of the longer growing season, increased omnivory and increased risk of algal blooms (Jeppesen et al, 2007, Kosten et al, 2009, which may offset the gains made by fish reductions. Clearly, more research on biomanipulation efforts in tropical and subtropical systems is needed (Jeppesen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%